2019
DOI: 10.1089/aut.2018.0004
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Service Utilization and Cost Among Adults with Autism Spectrum Disorders in a U.S. Integrated Health Care System

Abstract: Objectives: To compare health care utilization patterns and cost among insured adults with autism spectrum disorder (ASD), adults with attention-deficit and hyperactivity disorder (ADHD), and adults with neither condition (general population [GP] controls). Method: We conducted a case-control study among adults (q18 years) who were members of Kaiser Permanente Northern California (KPNC) for at least 9 months each year from 2008 to 2012. Cases (N = 1507) were adults with an ASD diagnosis (ICD-9-CM 299.0-299.8) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 49 publications
6
98
0
1
Order By: Relevance
“…Contrary to our hypothesis, individuals in the ASD‐only cohort did not significantly differ from population controls on the rates of ACS admissions. The only studies of ACS admissions in ASD in the literature [Carbone et al, ; Zerbo et al, ] did not differentiate between those with and without ID. Our results suggest that ID status may be driving the findings of increased ACS utilization in ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to our hypothesis, individuals in the ASD‐only cohort did not significantly differ from population controls on the rates of ACS admissions. The only studies of ACS admissions in ASD in the literature [Carbone et al, ; Zerbo et al, ] did not differentiate between those with and without ID. Our results suggest that ID status may be driving the findings of increased ACS utilization in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when compared to typically developing children, those with ASD have higher total charges and longer length of stay for ACS admissions [Carbone et al, 2015]. A recent study in the adult population found that the proportion of adults with ACS admissions was significantly higher among those with ASD relative to those with ADHD, but a difference was not observed between adults with ASD and the general population [Zerbo et al, 2018]. The present study seeks to add to the growing body of literature on the incidence of ACS admissions in individuals with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Autistic adults experience a greater number of co-occurring physical and mental health conditions than non-autistic adults (Croen et al, 2015;Fortuna et al, 2016), greater healthcare costs (Zerbo et al, 2019), higher rates of premature mortality (Hirvikoski et al, 2016), and higher inpatient mortality rates (Akobirshoev, Mitra, Dembo, & Lauer, 2020). Not surprisingly, studies have also found that autistic adults experience significant healthcare disparities, with higher reported rates of unmet healthcare needs, higher emergency department visits, lower use of preventive services, and lower ratings of patient-provider communication as compared to nonautistic adults (Nicolaidis et al, 2013).…”
Section: Healthcare Provider Self-efficacy Scalementioning
confidence: 99%
“…Specifically, autistic adults have more frequent co-occurring physical and mental health conditions (Croen et al, 2015;Fortuna et al, 2016) with higher rates of premature mortality (Hirvikoski et al, 2016) and inpatient mortality (Akobirshoev, Mitra, Dembo, & Lauer, 2019). They also have greater overall healthcare utilization and costs (Zerbo et al, 2019) and higher use of the emergency department (Nicolaidis et al, 2013;Vohra, Madhavan, & Sambamoorthi, 2016), with lower use of recommended preventative services, such as Papanicolaou smears (Nicolaidis et al, 2013;Zerbo et al, 2019). Similarly, studies focused on quality of care have found that autistic adults have greater unmet healthcare needs, lower satisfaction with patient provider communication, and more barriers to care than non-autistic adults (Mason et al, 2019;Nicolaidis et al, 2013;Raymaker et al, 2017).…”
Section: Instruments To Assess Healthcare Interventionsmentioning
confidence: 99%